THE USE OF CASSAVA PEEL (Manihot utilisima) FERMENTATION IN THE RATION ON THE FAT OF MALE LOCAL SHEEP - Ari Andani Nasution; Hasnudi; Nurzainah Ginting; Sayed Umar; Hamdan (Talenta Publisher, 2018)
ARI ANDANI NASUTION, 2018: The Use Of Cassava Peel (Manihot Utilisima) Fermentation In The Ration On The Fat Of Male Local Sheep Under supervised by HASNUDI and NURZAINAH GINTING. This study aims to determine how much influence the use of cassava peel (Manihot utilisima) fermentation in the rations on fat percentage of male local sheep. The research was conducted at the farm of Mr. Praditya located in Medan, in September-December 2017. The treatmen design used Completely Randomized Design (RAL) with 4 treatments and 5 replications. Using 20 local rams with an average of 10.18 ± 1 kg. The treatment provided is P0 (Cassava peel Non Fermentation), P1 (Cassava peel Fermentation 20%), P2 (Cassava peel Fermentation 40%), and P3 (Cassava peel Fermentation60%). The results showed that the average the percentage of subcutaneous fat of sheep of highest P3= 2.04 dan low P0= 1.10 (kg/head). Average percentage of abdomen fat of highest P0= 2.364 and low P3= 2.148 (kg/head). Average percentage of heart of highest P0P2P3= 0.204 and low P1= 0.198 (kg/head). Average percentage of kidneys fat of highest P2= 0.300 and low P0= 0.24 (kg/head). Average percentage of pelvis fat of highest P3= 0.284 and low P0= 0.262 (kg/head). The conclusion of this research is the high use of fermented cassava peel in the ration can increase the percentage of subcutaneous fat and percentage of pelvis fat, butcauses the percentage of abdo men fat percentage of heart, and percentage of kidneys fat.